The effects of continuous positive airway pressure therapy withdrawal on cardiac repolarization: data from a randomized controlled trial. - Rossi, V; Stoewhas, A; Camen, G; Steffel, J; Bloch, K; Stradling, JR; Kohler, M (2012)
AIMS: The preliminary evidence supports an association between obstructive sleep apnoea (OSA), disturbed cardiac repolarization, and consequent cardiac dysrhythmias. The aim of the current trial was to assess the effects of continuous positive airway pressure (CPAP) therapy withdrawal on the measures of cardiac repolarization in patients with OSA. METHODS AND RESULTS: Forty-one OSA patients established on CPAP treatment were randomized to either CPAP withdrawal (subtherapeutic CPAP) or continue therapeutic CPAP for 2 weeks. Polysomnography was performed, and indices of cardiac repolarization (QT(c), TpTe(c) intervals) and dispersion of repolarization (TpTe/QT ratio) were derived from 12-lead electrocardiography (ECG) at baseline and 2 weeks. Continuous positive airway pressure withdrawal led to a recurrence of OSA. Compared with therapeutic CPAP, subtherapeutic CPAP for 2 weeks was associated with a significant increase in the length of the QT(c) and TpTe(c) intervals (mean difference between groups 21.4 ms, 95% CI 11.3-1.6 ms, P < 0.001 and 14.4 ms, 95% CI 7.2-21.5 ms, P < 0.001, respectively) and in the TpTe/QT ratio (mean difference between groups 0.02, 95% CI 0.00-0.03, P = 0.020). There was a statistically significant correlation between the change in apnoea/hypopnoea index (AHI) from baseline, and both the change in the QT(c) interval and the TpTe(c) interval (r = 0.60, 95% CI 0.36-0.77, P < 0.001 and r = 0.45, 95% CI 0.17-0.67, P = 0.003, n = 41, respectively). CONCLUSION: Continuous positive airway pressure withdrawal is associated with the prolongation of the QT(c) and TpTe(c) intervals and TpTe/QT ratio, which may provide a possible mechanistic link between OSA, cardiac dysrhythmias, and thus sudden cardiac death.